Pengaruh Gaya Kepemimpinan, Motivasi, dan Disiplin Kerja terhadap Kinerja Auditor pada KAP di Kota Surabaya - Regita Permata Sari; Ec. Muslimin (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aim the determined they effects of leadership styles, motivations, and works disciplin on the performances of auditors at KAP in Surabaya. Primary data obtained through questionnaires. They are three independents variable in this studying, namely Leadership Style, Motivation, and Work Disciplined. One dependent variable is Auditor Performance at KAP in Surabaya. The sampling techniq use is simple random sampling methode to obtain a sample of 84 auditors who work at KAP Surabaya. From the results of the research conducted, the results are obtained: 1) Leadership style influences auditor performance; 2) Motivation influences auditor performance; 3) Work Discipline affects the auditor's performance. Researchers should further incorporate new variables into research, such as organizational climate, work ability or environmental factors. So that from these variables will get clearer results regarding the factors that will have an impact on the auditor's performance. Adding a large number of samples than this research. With the large number of samples used, the research results obtained will be more detailed and convincing in making decisions. Keywords: Leadership style, Motivation, Work discipline, Performances Auditor.